Development and evaluation of new artificial diet for mass rearing Hypothenemus hampei ( Coleoptera: Scolytidae) - PORTILLA, MARIBEL (Revista Colombiana de Entomología, 2000)
A new artificial diet called CENIBROCA (C) was developed for rearing coffee berry borer. It has fewer ingredients, good characteristics of nutrition to the target pest. good consistency keeps humidity longer, has low contamination, and is easy to prepare. Its reproductive potential and rate of increase were evaluated and compared with the following diets: Diet 140 (A), developed in Mexico in 1993; ECOBROVILL-160 (B), developed in Mexico in 1995, which is a simplification of the diet (A); and parchment coffee (D), the natural medium of rearing coffee berry borer used since 1989. Diets A, B, and C were poured into 50x10 mm glass tubes. Each tube contained 1 mi of diet and a recently emerged female. Parchment coffee was evaluated by individual infestation in the same way as an artificial diet. On evaluation after 40 days, diet Chad a mean production of 53,9 ± SD=6,3 insects per tube of diet, followed by diets Aand B with a mean production of 46,0 ± SD=6,1 and 40,1 ± SD=8,9 insects percent of diet respectively, the lowest production was for parchment coffee with 26,9 ± SD=5 insects of CBB. At 60 days, 254,6 ± SD=80,0 stages (50% were eggs, probably the third generation) were found on CENIBROCA, showing a significant difference (p<0,05) in relation to the diets, 140 with a mean production of 125,8 ± 49,4 states and 107,5 ± 50,9 to ECOBROVILL, respectively. The highest reproductive rate ( R0 ) and the maximum values of the intrinsic rate of increase (rm) of CBB were found in artificial diet C.